2020
DOI: 10.21037/atm.2020.02.57
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogen deprivation on memory and expression of related proteins in ovariectomized mice

Abstract: Background: The ovariectomized (OVX) rodent model is most widely used for studying the influence of estrogen deprivation on memory. However, the results of these studies are inconsistent, in that the memory of OVX rodents shows either impairment or no change. These inconsistent outcomes increase the difficulty of researching neurochemical mechanisms and evaluating drug efficacy. One possible explanation for these discrepancies might be that the time point for memory examination after OVX varies considerably am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…However, OVX females in our experiment did not exhibit recognition memory impairment after 4 weeks of OVX (it was 4 weeks after OVX when NORT was performed), as the sham and OST-treated groups did not outperform these OVX mice in the time spent exploring the novel object. Our results is in agreement with a previous report that 4 week OVX did not alter recognition memory (Tao et al, 2020) but not in agreement with another study in which 4 week OVX impaired recognition memory in the NORT in mice. Actually, there is a variation in the duration of OVX across studies reporting conflicting results (Fonseca et al, 2013;Mitra et al, 2016;Aggarwal et al, 2019;Tao et al, 2020), and this seems to be a contributing factor for these conflicting findings.…”
Section: Osthole Improved Ovariectomy-induced Deficits In Spatial Learning and Memory Recognition Memory And Sociabilitysupporting
confidence: 89%
See 1 more Smart Citation
“…However, OVX females in our experiment did not exhibit recognition memory impairment after 4 weeks of OVX (it was 4 weeks after OVX when NORT was performed), as the sham and OST-treated groups did not outperform these OVX mice in the time spent exploring the novel object. Our results is in agreement with a previous report that 4 week OVX did not alter recognition memory (Tao et al, 2020) but not in agreement with another study in which 4 week OVX impaired recognition memory in the NORT in mice. Actually, there is a variation in the duration of OVX across studies reporting conflicting results (Fonseca et al, 2013;Mitra et al, 2016;Aggarwal et al, 2019;Tao et al, 2020), and this seems to be a contributing factor for these conflicting findings.…”
Section: Osthole Improved Ovariectomy-induced Deficits In Spatial Learning and Memory Recognition Memory And Sociabilitysupporting
confidence: 89%
“…Our results is in agreement with a previous report that 4 week OVX did not alter recognition memory (Tao et al, 2020) but not in agreement with another study in which 4 week OVX impaired recognition memory in the NORT in mice. Actually, there is a variation in the duration of OVX across studies reporting conflicting results (Fonseca et al, 2013;Mitra et al, 2016;Aggarwal et al, 2019;Tao et al, 2020), and this seems to be a contributing factor for these conflicting findings. For example, impaired recognition memory in mice in the NORT was found after 1 week OVX (Mitra et al, 2016).…”
Section: Osthole Improved Ovariectomy-induced Deficits In Spatial Learning and Memory Recognition Memory And Sociabilitysupporting
confidence: 89%
“…On the other hand, Emodin is involved in autophagy and cognitive dysfunction during the neurons’ injury. For example, Emodin could inhibit aggregation of amyloid β peptide 1–42 and improve cognitive deficits in Alzheimer’s disease [14]. Moreover, Emodin could alleviate sepsis-induced injury via inducing autophagy [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…This result suggested that downregulation of BDNF/TrkB signaling may contribute to the neuronal injury. Moreover, inactivation of BDNF/TrkB signaling could result in promotion of cell apoptosis, inhibition of cell autophagy, and upregulation of inflammatory responses [9, 14, 17]. Based on these data, it can be supposed that BDNF/TrkB signaling might act as a key mediator in progression of SAE.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in numerous studies, it was shown that E 2 enhances memory consolidation 9 . The particular role of BDNF/TrkB with respect to E 2 ‐induced memory consolidation was also recently reported 65–68 …”
Section: Discussionmentioning
confidence: 70%